2006
DOI: 10.1002/uog.2630
|View full text |Cite
|
Sign up to set email alerts
|

The extent of endosonographic anal sphincter defects after primary repair of obstetric sphincter tears increases over time and is related to anal incontinence

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
4
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 29 publications
8
44
4
3
Order By: Relevance
“…This finding is similar to two other recent studies. Stark et al found an association between an increasing anal endosonographic defect score (range, 0-16) and the Wexner Anal Incontinence Questionnaire, after repair of an obstetric anal sphincter laceration [17]. Mahoney et al found that endosonographic IAS defects, but not EAS defects, were predictive of anal incontinence after repair of obstetric anal sphincter lacerations [18].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to two other recent studies. Stark et al found an association between an increasing anal endosonographic defect score (range, 0-16) and the Wexner Anal Incontinence Questionnaire, after repair of an obstetric anal sphincter laceration [17]. Mahoney et al found that endosonographic IAS defects, but not EAS defects, were predictive of anal incontinence after repair of obstetric anal sphincter lacerations [18].…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric sphincter defects repaired primarily at the time of delivery may increase in size with time, and the size of the defect corresponds to an increased risk of fecal incontinence [ 29 ]. Several studies have demonstrated that patients with persisting sphincter defects after overlapping sphincteroplasty have impaired outcomes [ 20 , 30 ].…”
Section: Anatomic Evaluation Ultrasound 2dmentioning
confidence: 99%
“…5a et 5b). Or, la persistance d'une rupture échographique est fortement liée au risque d'incontinence anale à long terme après l'accouchement [23,24]. De plus, nous avons observé [2] que les déchirures du périnée cotées stades 1 ou 2 par l'obstétricien (respectant donc en théorie le sphincter) étaient souvent associées à une rupture sphinctérienne ignorée (stade 1 : neuf ruptures sphinctériennes sur 48 parturientes et stade 2 : quatre ruptures sphinctériennes sur quatre parturientes).…”
Section: Facteurs De Risque De Lésion Du Nerf Honteux Interneunclassified